Surface modification of graphene and fullerene with Sulfur (S), Selenium (Se), and Oxygen (O): DFT Simulation for enhanced zidovudine delivery in HIV treatment - Faith O. Akor; Godwin D. Edo; Favour A. Nelson; Abasifreke U. Johnson; Solomon O. Iyam; Muhammad N. Abubakar; Alpha O. Gulack; Chioma B. Ubah; Bassey O. Ekpong; Innocent Benjamin (BMC Chemistry, 2024)
Abstract HIV is one of the most threatening health conditions with a highly increasing rate, affecting millions of people globally, and from its time of discovery until now, its potential cure cannot be explicitly defined. This challenge of having no/low effective drugs for the subjected virus has called for serious attention in the scientific world of virus disease therapeutics. Most of these drugs yields low effectiveness due to poor delivery; hence, there is a need for novel engineering methods for efficient delivery. In this study, two nanomaterilas (graphene; GP, and fullerene; C60) were modelled and investigated with sulfur (S), selenium (Se), and oxygen (O) atoms, to facilitate the delivery of zidovudine (ZVD). This investigation was computationally investigated using the density functional theory (DFT), calculated at B3LYP functional and Gd3bj/Def2svp level of theory. Results from the frontier molecular orbital (FMO), revealed that the GP/C60_S_ZVD complex calculated the least energy gap of 0.668 eV, thus suggesting a favourable interactions. The study of adsorption energy revealed chemisorption among all the interacting complexes wherein GP/C60_S_ZVD complex (-1.59949 eV) was highlighted as the most interacting system, thereby proving its potential for the delivery of ZVD. The outcome of this research urges that a combination of GP and C60 modified with chalcogen particularly, O, S, and Se can aid in facilitating the delivery of zidovudine.